2021
DOI: 10.1021/acs.jmedchem.1c00420
|View full text |Cite
|
Sign up to set email alerts
|

Development of HDAC Inhibitors Exhibiting Therapeutic Potential in T-Cell Prolymphocytic Leukemia

Abstract: Epigenetic targeting has emerged as an efficacious therapy for hematological cancers. The rare and incurable T-cell prolymphocytic leukemia (T-PLL) is known for its aggressive clinical course. Current epigenetic agents such as histone deacetylase (HDAC) inhibitors are increasingly used for targeted therapy. Through a structure–activity relationship (SAR) study, we developed an HDAC6 inhibitor KT-531, which exhibited higher potency in T-PLL compared to other hematological cancers. KT-531 displayed strong HDAC6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…53 Other fluorination/halogenation patterns were also tested in a recent SAR study, which revealed that the tetrafluoro analogs demonstrated superiority in terms of HDAC6 potency, selectivity, and cellular efficacy. 54 Compound 5a retained potency in the functional inhibition assay (Electrophoretic mobility shift assay (EMSA), Nanosyn Inc., USA) against HDAC6 (IC 50 = 9.8 nM) with 207-fold selectivity for HDAC6 over the next most potently hit HDAC (all 11 Zn 2+ -dependent HDAC isozymes evaluated). This compared favorably to the Given the promising data, an SAR test of the parent scaffold was conducted (Tables 1 and 2 and Table S2).…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…53 Other fluorination/halogenation patterns were also tested in a recent SAR study, which revealed that the tetrafluoro analogs demonstrated superiority in terms of HDAC6 potency, selectivity, and cellular efficacy. 54 Compound 5a retained potency in the functional inhibition assay (Electrophoretic mobility shift assay (EMSA), Nanosyn Inc., USA) against HDAC6 (IC 50 = 9.8 nM) with 207-fold selectivity for HDAC6 over the next most potently hit HDAC (all 11 Zn 2+ -dependent HDAC isozymes evaluated). This compared favorably to the Given the promising data, an SAR test of the parent scaffold was conducted (Tables 1 and 2 and Table S2).…”
Section: ■ Resultsmentioning
confidence: 99%
“…First, since HDAC6 does not have a reactive and accessible cysteine proximal to the catalytic tunnel, the electron-deficient electrophilic pentafluorobenzene sulfonamide (PFBS) group was considered an unnecessary metabolic liability and prompted the design of the less reactive N -hydroxy-4-(((2,3,4,5-tetrafluoro- N -isopropylphenyl)­sulfonamido)­methyl)­benzamide homolog 5a ( NN-390 ) . Other fluorination/halogenation patterns were also tested in a recent SAR study, which revealed that the tetrafluoro analogs demonstrated superiority in terms of HDAC6 potency, selectivity, and cellular efficacy . Compound 5a retained potency in the functional inhibition assay (Electrophoretic mobility shift assay (EMSA), Nanosyn Inc., USA) against HDAC6 (IC 50 = 9.8 nM) with 207-fold selectivity for HDAC6 over the next most potently hit HDAC (all 11 Zn 2+ -dependent HDAC isozymes evaluated).…”
Section: Resultsmentioning
confidence: 99%
“…61 The lysine/histone deacetylases (K/HDAC) are an established epigenetic therapeutic target. In this collection there are reports of HDAC inhibitors being investigated for the treatment of T-cell prolymphocytic leukemia 62 and the repurposing of human HDAC6 inhibitors to treat multi-drugresistant malaria-causing parasites. 63 There is also a Perspective discussing the potential for using selective HDAC6 inhibitors as a treatment for aspects of cystic fibrosis-associated lung disease.…”
Section: ■ Acs Pharmacology and Translational Sciencementioning
confidence: 99%
“…The lysine/histone deacetylases (K/HDAC) are an established epigenetic therapeutic target. In this collection there are reports of HDAC inhibitors being investigated for the treatment of T-cell prolympho­cytic leukemia and the repurposing of human HDAC6 inhibitors to treat multi-drug-resistant malaria-causing parasites . There is also a Perspective discussing the potential for using selective HDAC6 inhibitors as a treatment for aspects of cystic fibrosis-associated lung disease .…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%